2016
DOI: 10.1080/19386362.2016.1198109
|View full text |Cite
|
Sign up to set email alerts
|

Axial and lateral load transfer of fibre-reinforced polymer (FRP) piles in soft clay

Abstract: This paper presents the results of an experimental investigation on the performance of fibre-reinforced polymer (FRP) piles in soft clay. The load transfer behaviour of small-scale FRP piles manufactured using either glass or carbon fibres is analysed and compared to that of traditional steel piles, in order to assess the viability of FRPs as piling materials. In addition, the effects of FRP material and fibre orientation on pile behaviour are investigated with the goal of identifying the optimal conditions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The soil condition is an essential component that must be addressed for FRP piles because piles are used to support massive constructions, yet most of the works discussed over FRP piles and do not include soil effects. In reality, there are fewer studies on FRP heaps than on traditional piles [30][31][32][33][34][35][36], and even fewer studies evaluate the influence of soil when examining FRP piles. The research among FRP piles with varying load regimes is not necessary, leaving a gap [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil condition is an essential component that must be addressed for FRP piles because piles are used to support massive constructions, yet most of the works discussed over FRP piles and do not include soil effects. In reality, there are fewer studies on FRP heaps than on traditional piles [30][31][32][33][34][35][36], and even fewer studies evaluate the influence of soil when examining FRP piles. The research among FRP piles with varying load regimes is not necessary, leaving a gap [35].…”
Section: Introductionmentioning
confidence: 99%
“…In reality, there are fewer studies on FRP heaps than on traditional piles [30][31][32][33][34][35][36], and even fewer studies evaluate the influence of soil when examining FRP piles. The research among FRP piles with varying load regimes is not necessary, leaving a gap [35]. Furthermore, due to their relative lack of rigidity, FRP piles necessitate greater care during construction than traditional piles.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional steel bars, FRP has extraordinary corrosion resistance and thermal expansion coefficient, which is close to that of concrete, making it an ideal material to replace steel in marine or coastal infrastructures 7,8 . Besides, it has been reported that the ultimate skin frictional resistance of FRP piles was 5%−40% higher than the steel piles 9,10 . With the promotion of FRP in foundations, the interface properties between FRP structure and soil have received a lot of attention in recent years due to their critical impacts on the integrity and stability of the structure‐soil system.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Besides, it has been reported that the ultimate skin frictional resistance of FRP piles was 5%−40% higher than the steel piles. 9,10 With the promotion of FRP in foundations, the interface properties between FRP structure and soil have received a lot of attention in recent years due to their critical impacts on the integrity and stability of the structure-soil system.…”
Section: Introductionmentioning
confidence: 99%
“…The geometry of the assessed micro-piles was similar to that described for the reinforcing elements within the current paper. Pando et al [ 13 ] and Valez et al [ 25 ] have tested and renovated the structures of composite piles. Valez et al, as well as fiberglass structures, also tested carbon fiber piles in stabilized and non-stabilized soft soils.…”
Section: Introductionmentioning
confidence: 99%